Gravidez ectópica bilateral e tuberculose pulmonar prévia: relato de caso - Almeida, Thaynara Sarmento Oliveira de (2020)
Ectopic pregnancy (EP) occurs when the blasctocyst inserts itself in a different location in the uterine cavity, occurring mainly in the fallopian tubes. The bilateral Ectopic Pregnancy (BEP) cases have an incidence of 2%, with only 250 cases reported in the world literature, and the main risk factor is fertilization in vitro. However, new studies indicate a possible relation with Pulmonary Tuberculosis (PT), and consequently with Genital Tuberculosis (GT), which fits into an even rarer portion in the literature of 13.2% of the cases of EP. This project aims to report na inconmum case of bilateral ectopic pregnancy in a patient with previous involvement of pulmonary tuberculosis at a maternity in João Pessoa - PB. A retrospective longitudinal case study of an exploratory, descriptive and qualitative nature, without controled group, was carried out by reading the medical records. This case is about a 27-year-old patient, G0P0, who was admitted to the emergency department with severe abdominal pain accompanied by mild vaginal bleeding and nausea, with approximately 24 hours of installation, and without the presence of the most known risk factors. The transvaginal Ultrasound Examination (USG TV) showed a picture suggestive of unilateral ectopic pregnancy with dilation of the left uterine tube and blood in the abdominal cavity, and the patient was referred for urgent exploratory laparotomy. In this, it was found that in fact it was a bilateral route ectopic pregnancy, as the right tube was dilated and ruptured, and the total bilateral salpingectomy was performed. Histopathological diagnosis confirmed the transoperative findings of bilateral tubal pregnancy. The paciente develop clinical improvement and was discharge at the hospital later. The literature on the relationship between BEP and tuberculosis is still scarce. Therefore, the present condition is rare and needs further studies to encourage the realization of a guideline to better guide the diagnosis and treatment, as well as an investigation into the outcome of genital tuberculosis in cases of GEB.